Perjanjian Dengan Jaminan Gadai Pada PT Pegadaian Cabang Tangerang - Muktamara, Savira Alia; Badriyah, Siti Malikhatun (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The development of the economic and monetary sector is now deemed necessary to further enhance the role of credit institutions on the basis of legal guarantees that meet the needs of the community. The government has provided various other credit/loan facilities through PT Pegadaian. The pawn agreement is made by the customer as the debtor providing the pawn and PT Pegadaian as the holder of the pawn. Pawn objects are movable objects with a few exceptions. The procedure for requesting credit until repayment is relatively easy without conditions which will cause new problems for customers. The approach method used is empirical juridical. The results of the research PT Pegadaian carry out its duties to help the community work well. The pawnshop is responsible for the maintenance and storage of the pawned goods by being insured. After the due date but the pawned goods are not taken or not redeemed is a form of default that occurs, the collateral goods will be auctioned with the applicable procedures. PT Pegadaian Tangerang Branch sometimes faces problems but all of them can be overcome by sticking to the company's mission, vision and goals, so that there is no prolonged dispute between customers and PT Pegadaian.